'Capitalism: what has gone wrong?': Who went wrong? Capitalism? The market economy? Governments? 'Neoliberal' economics?. (8th November 2021) - Hellwig, Martin
Abstract: The paper contributes to a symposium of the Oxford Review of Economic Policy on 'Capitalism: What has Gone Wrong, What Needs to Change, and How can it be Fixed?'. The analysis starts from the observation that, in the United States, the United Kingdom, and continental Europe, widespread discontent has become an important political force. I attribute this discontent to a sense of unfairness in developments of the past few decades. I relate this sense of unfairness to: (i) negative effects of structural change, including joblessness and regional decline, (ii) the observation of extraordinary growth in executive remuneration and financial-sector remuneration, coupled with government bailouts in the global financial crisis, and (iii) changes in public policy and public discourse, with a retrenchment of public services and public investment, except for bailouts and a focus on 'efficiency', the meaning of which is driven by the perceptions of corporate executives rather than standard welfare economics. To capture these developments, one needs to think about 'capitalism' in the sense of French capitalisme or German Kapitalismus, with a focus on the symbiosis of wealth and power, including the elimination of competition, rather than merely another term for the market economy.